2003
DOI: 10.1111/j.1747-5457.2003.tb00022.x
|View full text |Cite
|
Sign up to set email alerts
|

A Sequence Stratigraphic Synthesis of the North African Mesozoic

Abstract: A synthesis of the sedimentology and sequence stratigraphy of the Mesozoic succession of North Africa is presented. Two chronostratigraphic correlation panels have been constructed at roughly right angles to each other across North Africa, in approximately E‐W and NNW‐SSE orientations. The panels illustrate the way in which sedimentology and hydrocarbon geology vary across the continent through time. The Mesozoic succession is divided into two sequences (NA 6, Early Triassic to Middle Cretaceous; and NA 7, Mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
(82 reference statements)
1
15
0
Order By: Relevance
“…Barremian-Aptian deposits are widespread in outcrops and the subsurface throughout North Africa (Guiraud et al, 2005). Provenance studies have shown that the Barremian-Aptian sediments were derived from the southern parts of studied areas (e.g., M'rabet, 1987;Carr, 2003).…”
Section: Paleogeography and Regional Trendsmentioning
confidence: 99%
“…Barremian-Aptian deposits are widespread in outcrops and the subsurface throughout North Africa (Guiraud et al, 2005). Provenance studies have shown that the Barremian-Aptian sediments were derived from the southern parts of studied areas (e.g., M'rabet, 1987;Carr, 2003).…”
Section: Paleogeography and Regional Trendsmentioning
confidence: 99%
“…2008). A late Cretaceous regional high subsidence rate, possibly associated with the Sirte collapse (Rusk 2001; Carr 2003), is effectively recognized in the Atlas mountains (Zouaghi 2005) and in Libya's Kufrah, Murzuq, Ghadami and Tripolitania basins. Through Cenozoic times, the progressive shortening between the African continental margin (Cyrenaica) and the Hellenic arc (Kempler & Garfunkel 1994; Rosenbaum et al .…”
Section: Regional Geodynamic Settingmentioning
confidence: 99%
“…(1988); this technique recommends interpreting the depositional sequences on seismic sections by identifying discontinuities at the base of reflection terminations and (3) stratigraphy as derived from onshore observations and drilling (Duronio et al . 1991), and regional geological synthesis (Carr 2003; Bosworth et al . 2008).…”
Section: The Different Seismic Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mesozoic succession is divided into two sequences. The first began from Triassic to middle Cretaceous with continental to shallow marine deposition (which includes the studied reservoir), where the second extend to late Cretaceous with shallow marine carbonates [5]. The Cenozoic formations are represented by a variety of clastic sediments from various Mio-Pliocene depositional environments ( [2], [3]).…”
Section: Geological Settingmentioning
confidence: 99%